A review of the health hazards posed by cobalt. (April 2013) - Paustenbach, Dennis J.; Tvermoes, Brooke E.; Unice, Kenneth M.; Finley, Brent L.; Kerger, Brent D.
Abstract Cobalt (Co) is an essential element with ubiquitous dietary exposure and possible incremental exposure due to dietary supplements, occupation and medical devices. Adverse health effects, such as cardiomyopathy and vision or hearing impairment, were reported at peak blood Co concentrations typically over 700 µg/L (8–40 weeks), while reversible hypothyroidism and polycythemia were reported in humans at ∼300 µg/L and higher (≥2 weeks). Lung cancer risks associated with certain inhalation exposures have not been observed following Co ingestion and Co alloy implants. The mode of action for systemic toxicity relates directly to free Co(II) ion interactions with various receptors, ion channels and biomolecules resulting in generally reversible effects. Certain dose–response anomalies for Co toxicity likely relate to rare disease states known to reduce systemic Co(II)-ion binding to blood proteins. Based on the available information, most people with clearly elevated serum Co, like supplement users and hip implant patients, have >90% of Co as albumin-bound, with considerable excess binding capacity to sequester Co(II) ions. This paper reviews the scientific literature regarding the chemistry, pharmacokinetics and systemic toxicology of Co, and the likely role of free Co(II) ions to explain dose–response relationships. Based on currently available data, it might be useful to monitor implant patients for signs of hypothyroidism and polycythemia starting at blood or serum Co concentrations above 100 µg/L. This concentration is derived by applying an uncertainty factor of 3 to the 300 µg/L point of departure and this should adequately account for the fact that persons in the various studies were exposed for less than one year. A higher uncertainty factor could be warranted but Co has a relatively fast elimination, and many of the populations studied were of children and those with kidney problems. Closer follow-up of patients who also exhibit chronic disease states leading to clinically important hypoalbuminemia and/or severe ischemia modified albumin (IMA) elevations should be considered.